2007
DOI: 10.1364/oe.15.010346
|View full text |Cite
|
Sign up to set email alerts
|

Densely integrated microring resonator based photonic devices for use in access networks

Abstract: Two reconfigurable optical add-drop multiplexers, operating in the second or third telecom window, as well as a 1x4x4 reconfigurable λ -router operating in the second telecom window, are demonstrated. The devices have a footprint less than 2 mm 2 and are based on thermally tunable vertically coupled microring resonators fabricated in Si 3 N 4 /SiO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The label extractor/eraser consists of pigtailed vertically coupled microring resonators fabricated in the Si N -SiO materials system [4] (high contrast materials system, ), with a pass-through port and a drop port as shown in Fig. 2(a).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The label extractor/eraser consists of pigtailed vertically coupled microring resonators fabricated in the Si N -SiO materials system [4] (high contrast materials system, ), with a pass-through port and a drop port as shown in Fig. 2(a).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Klein et al [71] have demonstrated thermally a tunable MRR-based ROADM for access networks. These devices have been fabricated in Si 3 N 4 /SiO 2 technology with a footprint of less than 2 mm 2 and they are capable of operating in the second or third telecom window.…”
Section: Technologies For Roadmsmentioning
confidence: 99%
“…The key elements of the network are the Wavelength Router (WR) situated in the Remote Node (RN) and the RSOA placed in the ONU. The WR is a matrix of microring resonators which are thermally tuned [3]. The example of an 8-port WR is given in Fig.…”
Section: Network Architecturementioning
confidence: 99%